Meta-analysis of Fragmented QRS as an Electrocardiographic Predictor for Arrhythmic Events in Patients with Brugada Syndrome - Meng, Lei; Letsas, Konstantinos P.; Baranchuk, Adrian; Shao, Qingmiao; Tse, Gary; Zhang, Nixiao; Zhang, Zhiwei; Hu, Dan; Li, Guangping; Liu, Tong (Frontiers in Physiology, 2017)
Fragmented QRS (fQRS) is an electrocardiographic marker related to ventricular fibrillation (VF) and sudden cardiac death (SCD) in various clinical settings. Current data regarding the prognostic significance of fQRS in Brugada syndrome (BrS) are contradictory. This meta-analysis aimed to evaluate the presence of fQRS as a risk stratification tool in BrS. Electronic databases (PubMed, EMBASE and Cochrane Library) were searched until May 2016. Eight observational studies accumulating data on 1,637 BrS patients (mean age: 47±11 years) were included in this meta-analysis. The mean follow-up duration ranged from 21 to 96 months. fQRS was found to be an independent predictor of future arrhythmic events in BrS (RR:3.88, 95% CI 2.26 to 6.65, p < 0.00001) with moderate heterogeneity (I2 = 54%, P=0.03). When analyzing VF as independent end-point, the RR for VF was 3.61, and its 95% CI was 2.11 to 6.18, p < 0.00001. This meta-analysis showed that BrS patients with fQRS are at high risk for future arrhythmic events. The presence of fQRS warrants prospective evaluation as valid arrhythmogenic risk marker in BrS.